Challenges of Bengal tiger (Panthera tigris tigris) conservation in the tropics: lessons learned from the Chitwan National Park of Nepal - Bhattarai, Bishnu Prasad (Jihočeská univerzita, 2012)
This research deals with the challenges of the conservation of tiger (Panthera tigris tigris) in the Chitwan National Park of Nepal and aims to be a model for tiger conservation in the tropical areas of other tiger range countries. Despite the high level of public concern and major investments during the last few decades for conservation, wild tigers continue to be under grave threat, and their preservation now requires, more than ever before, using reliable ecological knowledge for their conservation interventions. In this dissertation, I investigated various factors that affect on tiger conservation in this park: population status of prey, dietary patterns of tiger and its impact on sympatric carnivores (e.g., leopard) and increasing human-wildlife conflicts, effects of habitat structures and human disturbances on prey and predator species abundance and distribution.
Challenges of Bengal tiger (Panthera tigris tigris) conservation in the tropics: lessons learned from the Chitwan National Park of Nepal
Keywords: Carnivores; Predators; Prey; Tiger; Leopard; Wild ungulates; Deer; Human disturbance; Chitwan National Park; Conservation; Habitat heterogeneity; Landscape fragmentation; poaching and illegal trade; Carnivores; Predators; Prey; Tiger; Leopard; Wild ungulates; Deer; Human disturbance; Chitwan National Park; Conservation; Habitat heterogeneity; Landscape fragmentation; poaching and illegal trade